2021
DOI: 10.1080/19768354.2021.1925741
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and gene expression patterns are widely altered in fetal growth restriction and associated with FGR development

Abstract: Fetal growth restriction (FGR) is the failure of the fetus toachieve its genetically determined growth potential, which increasesrisks for a variety of genetic diseases, such as type 2 diabetes mellitus, coronary artery disease, and stroke, during the lifetime. The dysregulation of DNA methylationis known to interact with environmental fluctuations, affect gene expressions comprehensively, and be fatal to fetus development in specific cases. Therefore, we set out to find out epigenetic and transcriptomic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Some altered miRNAs (miR-28-5p and miR-301a-3p) showed sexually dimorphic expression in FGR pregnancies. Lee et al 40 demonstrated three genes (INS, MEG3, and ZFP36L2) implicated in epigenetic imprinting, suggesting that abnormal DNA methylation patterns are likely to alter gene expression, INS is a gene coding insulin associated with glucose metabolism in fetal development. 41 Homeobox genes such as HLX play a critical role in trophoblast function and involve molecular and cellular mechanisms.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
“…Some altered miRNAs (miR-28-5p and miR-301a-3p) showed sexually dimorphic expression in FGR pregnancies. Lee et al 40 demonstrated three genes (INS, MEG3, and ZFP36L2) implicated in epigenetic imprinting, suggesting that abnormal DNA methylation patterns are likely to alter gene expression, INS is a gene coding insulin associated with glucose metabolism in fetal development. 41 Homeobox genes such as HLX play a critical role in trophoblast function and involve molecular and cellular mechanisms.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
“…HERVs are dynamically expressed during early embryogenesis and differentiation [ 75 ]. Although several HERV subfamilies are expressed in a tight spatiotemporal mode in early human embryos, HERV expression is largely repressed in early human embryos, and its derepression is associated with lethality at various embryonic stages [ 30 , 76 ]. It has been reported that ERV derepression triggered upon acute perturbation of the repression machinery generates ERV RNAs at hundreds or maybe even thousands of genomic loci, disrupting phase-separated transcriptional condensates enriched in RNA polymerase II in the nucleus [ 12 ].…”
Section: Reproductionmentioning
confidence: 99%
“…However, a sudden move to over-nutrition exposes the inadequate beta-cell reserve and predisposition to T2DM [11,12]. Studies of cord blood from growth-restricted infants have shown epigenetic alterations of genes involved in metabolic pathways [13,14]. Interestingly, low birth weight in full-term infants has been shown to have the same effect (reduction) on insulin sensitivity later in life as is seen in those born preterm with appropriate-for-gestational-age birth weight [15].…”
Section: Birth Weightmentioning
confidence: 99%